DYNAMICS OF WBC INDICES IN POULTRY FOLLOWING ENROFLOXACIN ADMINISTRATION: COMPARATIVE ANALYSIS - Anna A. Moiseeva; Andrey A. Prisnyi; Vladimir N. Skvortsov (Siberian Journal of Life Sciences and Agriculture, 2022)
The goal of our research was to assess the effect of Enrofloxacin (fluoroquinolone antibacterial drug) on WBC indices of different kinds of poultry at young age. In order to study the dynamics we performed two series of experiments employing groups as follows: Group 1 – control group (one-day-old chicks, receiving pure drinking water), Group 2 – experimental group (one-day-old chicks, receiving Enrofloxacin via drinking water at concentration 200 g/L for 10 consecutive days), Groups 3 and 4 were made with one-day-old ducklings, the experiment design was the same as with chicks. Blood samples were drawn from every bird on Day 1, Day 3, Day 5, Day 7 and Day 9 after the drug withdrawal. We performed differential leukocyte count, leukogram was made and we also calculated leukocyte (hematological) indices. The data analysis showed reliable changes of blood indices both in chicks and in ducklings. The greatest changes in the results of both experimental groups as compared to the control groups were observed on Day 7, but they were not lasting. We observed more pronounced and lasting changes in the leukogram of Group 2, while duckling blood showed reliable changes of leukocyte indices. But all in all dynamics in WBC indices that we observed did not show toxic effect of the drug on bird organism.